2009
DOI: 10.1016/j.nurt.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Operative Techniques for Gliomas and the Value of Extent of Resection

Abstract: Summary:Refinement of neurosurgical technique has enabled safer operations with more aggressive outcomes. One cornerstone of modern-day practice is the utilization of intraoperative stimulation mapping. In addition to identifying critical motor pathways, this technique can be adapted to reliably identify language pathways. Given the individual variability of cortical language localization, such awake language mapping is essential to minimize language deficits following tumor resection. Our experience suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(103 citation statements)
references
References 108 publications
(52 reference statements)
3
87
0
13
Order By: Relevance
“…The extent of surgical resection was not a statistically significant predictor of survival, and yet there was a very strong trend in favor of resection compared with biopsy (p = 0.06). That finding is consistent with the existing literature on surgical resection for adult glioma, although no randomized data are available to support a causal effect [27][28][29][30] . It remains possible that some of the effect is a result of very poor survival in patients in whom surgical resection was not possible.…”
Section: Discussionsupporting
confidence: 88%
“…The extent of surgical resection was not a statistically significant predictor of survival, and yet there was a very strong trend in favor of resection compared with biopsy (p = 0.06). That finding is consistent with the existing literature on surgical resection for adult glioma, although no randomized data are available to support a causal effect [27][28][29][30] . It remains possible that some of the effect is a result of very poor survival in patients in whom surgical resection was not possible.…”
Section: Discussionsupporting
confidence: 88%
“…[13,14] Ekstensif rezeksiyonun prognozla ilişkili olduğuna dair sayısız data olmasına rağmen, sağkalımı artırdığına ait birinci sınıf kanıt yoktur. [4,13] Cerrahi, semptomlu ve nörolojik fayda, net patolojik tanı ve moleküler analiz için gerekli dokunun elde edilmesi açısından şarttır.…”
Section: Discussionunclassified
“…[13,14] Ekstensif rezeksiyonun prognozla ilişkili olduğuna dair sayısız data olmasına rağmen, sağkalımı artırdığına ait birinci sınıf kanıt yoktur. [4,13] Cerrahi, semptomlu ve nörolojik fayda, net patolojik tanı ve moleküler analiz için gerekli dokunun elde edilmesi açısından şarttır. [4] Hasta grubumuzda artmış rezeksiyonun sağkalıma faydası olduğu gözlenmiş; bir, üç, beş yıllık genel sağkalım sırasıyla total eksizyon ile %55, %19.9, %9.9 subtotal eksizyon ile %40.8, %14, %14 yanlızca biyopsi ile %16, %0, %0 olarak bulunmuştur (p<0.001).…”
Section: Discussionunclassified
“…Undoubtedly, CSES has gained a prominent role in neurosurgery above all because a large number of studies worldwide have shown a clear advantage in terms of usefulness, safety, and neurological and oncological outcomes (Berger 1994;Duffau et al 2005;Duffau 2006;Kim et al 2009;Sanai & Berger 2009;De Benedictis et al 2010;Spena et al 2010). The spatial accuracy and the ability to perform functional resection (that is, a resection in which limits are represented by spared functions) have met the approval of many neurosurgeons, who now use CSES routinely.…”
Section: Brain Mapping In Neurosurgery: Criticisms and Future Perspecmentioning
confidence: 99%
“…The ability to maximize resection while preserving a satisfying functional outcome is of particular interest in brain gliomas for two reasons: first, gliomas mostly affect young adults in full social and working activity, so functional outcome is of the utmost relevance. Second, many different studies (Berger 1994;Keles et al 2001;Sanai & Berger 2009;Stendel 2009) have by now demonstrated that total or subtotal resection has a clear impact on survival and, for LGG (low grade glioma), on malignant transformation, and that the extent of resection is strongly affected by eloquence of the tumor location (Chang et al 2008). In some cases, CSES can also guide in the detection of the safest route for removing purely subcortical tumors.…”
Section: Introduction and Indicationsmentioning
confidence: 99%